The Relationship Between Individual Factors And Smoking Behavior In Adolescents In The Working Area Of Rawasari Community Health Center - Fajrina Hidayati; Budi Aswin (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
AbstractSmoking is a bad habit that if left unchecked will cause health problems that lead to death. In addition, smoking is closely related to various neurological, cardiovascular, and pulmonary diseases. Cigarettes can also cause other people around the smoker to get diseases due to being a passive smoker. Factors that influence smoking behavior include knowledge and attitudes toward smoking. This study aimed to analyze the relationship between individual factors and adolescent smoking behavior in the Rawasari Health Center, Jambi City working area. This research is a quantitative study with a cross-sectional design. The population in this study were all male adolescents in the working area of the Rawasari Health Center with an age range of 15-24 years, namely 6.490 youths and the sample in this study was 100 adolescents. Data analysis using chi-square. The results of the study most of the respondents smoked, namely as many as 70 respondents (70%). Most of the respondents knowledge was low about smoking, its ingredients, the effects or health impacts caused, and the disadvantages of smoking, namely as many as 69 respondents (69%). More than half of the respondents (59%) have a supportive attitude towards smoking as many do not agree (38 respondents) not to smoke rather than creating a bad image in their environment. Based on the analysis there is a relationship between knowledge (p=0.000) and attitude (p=0.000) with smoking behavior in adolescents (p <0.05). There needs to be direction and guidance from parents, the role of puskesmas officers to conduct counseling about the dangers of smoking, and appeals not to smoke.Keywords: Male Youth, Rawasari Health Center, Smoking Behavior